Evaluation and characterization of nutritional, microbiological and sensory properties of beet greens - Fernandez, María Verónica (2017)
Growing interest of consumers on incorporate healthy foods into their diets has triggered extensive research in finding and developing new food products that meet their expectations. Leaves of beet plants are an alternative source of appreciable value albeit they are usually discarded at the time of beetroot harvest. The aim of this study was to evaluate and characterize the nutritional, microbiological and sensory quality of beet greens as a prelude to the development of new products from them. Beet greens represents approximately 50% of harvested material. The proximate composition of leaves and its anti-nutritional factors (oxalate, phytates and tanins) were in the range of commonly consumed leafy vegetables, standing out for its high contents of protein, fat, fiber and iron and low content of phytates and tanins. Contents of phytochemical compounds, especially carotenoids and betalains, were higher than those reported for commonly consumed leafy vegetables, resulting in a high antioxidant potential. Microbiological counts were in the typical range for fresh consumed leafy vegetables while, sensorial quality resulted adequate with highly appreciated characteristics in beet greens such as red veins and green blade. This work sets the basis for several recovery possibilities such as development of a minimally processed product for fresh consumption and the extraction of phytochemical compounds from this resource.